Politik Hukum Putusan MK No. 46/PUU-VIII/2010 Tentang Status Anak di Luar Nikah: Upaya Membongkar Positivisme Hukum Menuju Perlindungan HAM - Asnawi, Habib Shulton (Mahkamah Konstitusi Republik Indonesia, 2013)
Protection of human rights (human rights) in the Constitution applies in Indonesia ever prove that one of the requirements for a state law is the guarantee of human rights. Indonesia assertion of law set forth in the 1945 amendment of Article 1 paragraph (3) “State of Indonesia is the Rule of Law”. The form states have laws on the protection of human rights in implementation by the Constitutional Court (MK) in Decision No. 46/PUU-VIII/2010 on the Status of Child Marriages outside. Political decisions of law sought to protect the rights of the child, in addition to trying to dismantle the positivistic-legalistic law, which for year’s had been shackled for justice and human rights. However, in Indonesia the law of the Constitutional Court reap the political pros and cons. Therefore, it is necessary socialization broadly relevant decision of the Court, the Court of law that political action are on the correct constitution, embodying the rule of law and democratic ideals for the sake of our nationhood and nation’s dignity. Constitutional Court’s decision is a wise choice and a step forward in the field of law for the defense of children’s rights that have long shackled Article 43 of the Act. N0. 1 of 1974 on Marriage. To be effective this decision the government should immediately respond with a set of supporting regulations that can be implemented by the Ministry of Religious Affairs and Ministry of Interior.